Proceedings of the 14th International Conference on Interaction Design and Children 2015
DOI: 10.1145/2771839.2771854
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the lived experience of adolescents with type 1 diabetes

Abstract: Type 1 diabetes affects approximately 1 in every 500 children in the UK. Although it is a lifelong condition, there are few if any overt manifestations, which can make it more difficult to meet people with the same condition. To avoid the risk of health complications, an emphasis is placed on a routine of selfmanagement behaviours. However, factors such as the desire to 'fit in' with the peer group may impede adherence and thus increase the probability of diminished health later in life. Creating appropriate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Additionally, research has also found that higher perceptions of social support are correlated with increased feelings of control over one's health condition (Evans and Connis, 1995;Wright, 2002). It is particularly important during the adolescent and teen years during which individuals develop their sense of self (Olsson et al, 2005;Webster et al, 2015). Social support is an overarching term that encompasses five types of support, including: informational, emotional, esteem, networking, and tangible (Cutrona and Suhr, 1992).…”
Section: Social Supportmentioning
confidence: 99%
“…Additionally, research has also found that higher perceptions of social support are correlated with increased feelings of control over one's health condition (Evans and Connis, 1995;Wright, 2002). It is particularly important during the adolescent and teen years during which individuals develop their sense of self (Olsson et al, 2005;Webster et al, 2015). Social support is an overarching term that encompasses five types of support, including: informational, emotional, esteem, networking, and tangible (Cutrona and Suhr, 1992).…”
Section: Social Supportmentioning
confidence: 99%
“…In fact, T1D-specific stigma and stigma by association with T2D leads to reluctance to disclose (Browne et al, 2014), with young adults describing helpful, neutral and negative reactions to disclosure (Dovey-Pearce et al, 2007). This is relevant to social support, as findings emphasize the value of sharing personal stories with others with T1D (Webster et al, 2015).…”
mentioning
confidence: 97%
“…Although PatientsLikeMe and Facebook users can communicate synchronously or asynchronously via private messaging and timeline posts, finding relevant and accurate information across many resources and at different points of the care process poses many challenges. Prior work has also explored the use of virtual spaces where patients can access a repository of advice organized by symptom, treatment, or common struggle [6,49]. However, the cognitive and physical effort required to navigate and find relevant support is something that patients and caregivers in the hospital are not always not capable of due to medications or treatments [39].…”
Section: Discussionmentioning
confidence: 99%